1974
DOI: 10.1111/j.1945-5100.1974.tb00075.x
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition of Major Elements and Heavy Trace Metals in Chondrites Parambù and Marilia

Abstract: The chemical composition of the newly observed fallen chondrites Parambù, 1967, and Marilia, 1971, was determined. Wet chemical methods were used for major elements analyses and the abundances of heavy trace elements from tungsten to uranium were determined by spark source mass spectrometry. The chemical composition confirmed the classification of Marilia as an H‐group chondrite by Avanzo et al. (1973): Parambù was classified as an LL‐group chondrite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Lauretta et al (2001) have reported bulk abundances of Hg of 294 ± 15 and 30 ± 1.5 ng•g − 1 for the Murchison and Allende carbonaceous chondrites, respectively. In addition, Shima et al (1974) have reported a bulk Hg analysis of 1330 ng•g −1 for the Parambu chondrite (state of Ceará, Brazil). The nature of the main meteorite impactor is under debate but short-lived Cr isotopic compositions of sedimentary rocks from the KTB, for some authors, point to a Hg-poor carbonaceous chondritetype bolide (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Lauretta et al (2001) have reported bulk abundances of Hg of 294 ± 15 and 30 ± 1.5 ng•g − 1 for the Murchison and Allende carbonaceous chondrites, respectively. In addition, Shima et al (1974) have reported a bulk Hg analysis of 1330 ng•g −1 for the Parambu chondrite (state of Ceará, Brazil). The nature of the main meteorite impactor is under debate but short-lived Cr isotopic compositions of sedimentary rocks from the KTB, for some authors, point to a Hg-poor carbonaceous chondritetype bolide (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…(1978), Okada etal. (1979), Shima (1974), Shima et al (1974) and Vilcsek (1959) were compiled for obtaining Ni/metal ratios. It was found that the H-and the L-group chondrites gave ratios 8.93 ± 0.73 (l o) % and 14.69 ± 1.92 (la) %*, respectively, which are not far from the above mean values; however, the ratios for L-group chondrites are rather variable.…”
Section: Discussionmentioning
confidence: 99%
“…**Decay constants for 4He and 4°Ar ages are given by Steiger and Jager (1977). Dodd (1981) and for LL-chondrites, mean value of the original data by Jarosewich (1966), Jarosewich and Mason (1969), , Wiik (1961, 1964) and Shima et al (1974) is taken. **After Van Schmus and Wood (1967).…”
Section: Date Of Fallmentioning
confidence: 99%